No margin, no mission : health-care organizations and the quest for ethical excellence - Pearson, Steven D.; Sabin, James E.; Emanuel, Ezekiel J., 1957- (Oxford University Press, 2003)
Can the ethical mission of health care survive among organizations competing for survival in the marketplace? On this question hinges not only the future of health care in the US, but that of the health care systems of all advanced countries. This book presents both an analytic framework and a menu of pragmatic answers. The team of authors, physician-ethicists from Harvard Medical School and the National Institutes of Health, worked with a consortium of health care organizations to explore some of the most challenging dilemmas in health care today: How can health plans determine medical necessity in a way that ensures quality care, controls costs, and builds trust with patients and physicians? What are the strategies for caring for vulnerable populations that meet their special needs without dramatically increasing costs? To answer these and other similar questions the authors blend ethical analysis with real-world example. The outcome is a rich analysis of the ethical challenges facing health care organizations, combined with tangible examples of exemplary methods to address these challenges.; This book will help health care leaders, regulators, and policy makers incorporate exemplary practices, and the underlying themes they embody, into the very heart and soul of health care organizations.